Effects of Air Pollution on Lung Function and Symptoms of Asthma, Rhinitis and Eczema in Primary School Children - Altuğ, Hicran; Gaga, Eftade Emine; Döğeroğlu, Tuncay; Özden, Özlem; Brunekreef, Bert; Meliefste, Kees; Hoek, Gerard; Van Doorn, Wim; ÖRNEKTEKİN, SERMİN (Springer Heidelberg, Tiergartenstrasse 17, D-69121 Heidelberg, Germany, 2013)
Health effects of ambient air pollution were studied in three groups of schoolchildren living in areas (suburban, urban and urban-traffic) with different air pollution levels in EskiAYehir, Turkey. This study involved 1,880 students aged between 9 and 13 years from 16 public primary schools. This two-season study was conducted from January 2008 through March 2009. Symptoms of asthma, rhinitis and eczema were determined by the International Study of Asthma and Allergies in Childhood questionnaire in 2008. Two lung function tests were performed by each child for summer and winter seasons with simultaneous ambient air measurements of ozone (O-3), nitrogen dioxide (NO2) and sulfur dioxide (SO2) by passive sampling. Effects of air pollution on impaired lung function and symptoms in schoolchildren were estimated by multivariate logistic regression analyses. Girls with impaired lung function (only for the summer season evaluation) were more observed in suburban and urban areas when compared to urban-traffic area ([odds ratio (OR) = 1.49; 95 % confidence interval (CI) 1.04-2.14] and [OR = 1.69 (95 % CI 1.06-2.71)] for suburban vs. urban-traffic and urban vs. urban-traffic, respectively). Significant association between ambient ozone concentrations and impaired lung function (for an increase of 10 mu g m(-3)) was found only for girls for the summer season evaluation [OR = 1.11 (95 % CI 1.03-1.19)]. No association was found for boys and for the winter season evaluation. No association was found between any of the measured air pollutants and symptoms of current wheeze, current rhinoconjunctivitis and current itchy rash. The results of this study showed that increasing ozone concentrations may cause a sub-acute impairment in lung function of school aged children.
Keywords: Air Pollution; Ambient Ozone; Summer; Children; ISAAC; Lung Function; North-American Children; Peak Expiratory Flow; Long-Term Exposure; Respiratory Symptoms; Pulmonary-Function; Risk-Factors; Function Growth; Early-Childhood; Acid Aerosols; Hava Kirliliği; Ortam Ozonu; Yaz; Çocuklar; Akciğer Fonksiyonu; Kuzey Amerika Çocukları; Pik Ekspirasyon Akışı; Uzun Süreli Maruz Kalma; Solunum Yolu Semptomları; Pulmoner Fonksiyon; Risk Faktörleri; İşlev Büyümesi; Erken Çocukluk; Asit Aerosolleri